28 Humoral response to SARS-CoV-2 vaccination among heart transplant recipients aged 18–70 years of age administered two doses of an adenoviral vector (ChAdOx1 nCoV-19) vaccine and a messenger RNA (BNT162b2) booster. (6th October 2022) - Tanner, R; ,; Perez-Garcia, C; Chan, G; Dempsey, E; Heffernan, E; O'Neill, J; Lynch, B; Hannan, M; Joyce, E
Abstract : Introduction: Solid-organ transplant (SOT) recipients have an excess mortality risk from severe acute respiratory syndrome coronavirus (SARS-CoV-2), while simultaneously initial reports have suggested blunted responses to messenger RNA (mRNA) vaccination. A paucity of data on adenoviral vector vaccines and heterologous booster use in SOT recipients exists. Hence, we undertook a two-phase study to firstly describe the safety and humoral response to two doses of the adenoviral vector ChAdOx1 nCoV-19 vaccine in our heart transplant population. The second phase sought to examine the humoral response to a heterologous mRNA booster in this patient cohort Methods: Heart transplant recipients aged 18 to 70 years of age were prospectively enrolled in this study. Participants had a serum blood sample drawn after each vaccination dose to test for total antibodies against the receptor-binding domain (RBD) of the spike (S) protein (anti-spike antibodies) using the quantitative Elecsys anti-SARS-CoV-2 S immunoassay. A screening questionnaire complemented with a serum sample testing for anti-nucleocapsid antibodies was employed to detect prior SARS-CoV-2. Participants were excluded if they had a history of SARS-CoV-2 infection or if they contracted the virus during the study period. Results: A total of 92 heart transplant patients (mean age 50±12 years, 29% female) were enrolled in the first phase of the study. All included patients had a negative anti-nucleocapsid antibody result and no history of SARS-CoV-2. At a mean of 12±2 weeks after the initial ChAdOx1 nCoV-19 vaccine 24% of patients (n=22) had a detectable antibody response, increasing significantly to 34.8% (n=32) 29 (IQR 28–31) days following dose 2, (p<0.001). In those patients eligible for phase 2 (n=80), 3rd dose 'booster' vaccination resulted in 56% (n=45) of the study cohort producing a positive antibody response 30 (IQR 28–33) days after inoculation ( figure 1 ). No serious adverse reaction to vaccination during phase 1 or 2 was recorded. Chronic kidney disease (CKD) stage ≥3 (OR 4.7, 95%CI 1.5–15, p=0.009) and mycophenolate use (OR 4.1, 95%CI 1.2–14, p=0.02) were independently associated with a non-detectable antibody response after the initial 2 doses of the viral vector ChAdOx1 nCoV-19 vaccine. Conclusions/Implications: Heart transplant recipients who received 2 doses of the ChAdOx1 nCoV-19 viral vector vaccine and a mRNA booster vaccine failed to develop a detectable antibody response in 44% of cases. These findings highlight the importance of maintaining protective measures for transplant recipients, particularly those on more intensive immunosuppressive regimens, both at a personal and public health level, as well as investigating additional strategies to protect this vulnerable patient cohort.